A case report of Polish cochineal larvae infestation of eyelid - Canleblebici, Mehmet; Balbaba, Mehmet (My University, 2024)
The Polish cochineal (Porphyrophora polonica), a scale insect, has been integral to the textile and dye industries of Europe and Central Asia for centuries, prized for its ability to produce a vivid red dye. This insect, although commonly associated with its utility in historical dyeing practices, seldom crosses paths with the medical field. However, an unusual case report from Akdağmadeni, a region renowned for its dense oak and pine forests which create a conducive environment for ticks, highlights a rare intersection. In this case report, the Polish cochineal larva, which was mistakenly diagnosed as a tick, was removed from the eyelid of a 57-year-old female patient, and the allergic reaction it caused is presented. The case underscores this rare infestation with the significance of accurate diagnosis in the prevention of unnecessary medical interventions.
Keywords: Eyelid; tick; Allergy of eye; cochineal; polish